2006
DOI: 10.1097/00001888-200603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Randomized Controlled Trial of Adjuvant Web-Based Teaching to Medical Students

Abstract: This randomized controlled trial provides Class I evidence that Web-based teaching as an adjunct to clinical experiences can significantly and durably improve medical students' learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 19 publications
2
54
0
1
Order By: Relevance
“…34 Multiple studies have demonstrated improved learning efficiency and knowledge retention using spaced education in surgical residencies and undergraduate medical education when material was delivered over months to years. 22,23,[25][26][27]35,36 Our study showed the utility of spaced education over a month-long rotation. Considerable attrition may have played a role in our inability to detect a significant difference in test performance at the 3-month follow up.…”
Section: Discussionmentioning
confidence: 57%
“…34 Multiple studies have demonstrated improved learning efficiency and knowledge retention using spaced education in surgical residencies and undergraduate medical education when material was delivered over months to years. 22,23,[25][26][27]35,36 Our study showed the utility of spaced education over a month-long rotation. Considerable attrition may have played a role in our inability to detect a significant difference in test performance at the 3-month follow up.…”
Section: Discussionmentioning
confidence: 57%
“…The largest of these 5 studies was conducted by Kerfoot et al, 18 who evaluated the effect of web-based urological cases on the knowledge of 286 medical students across 4 medical schools in the USA. Students were randomized to 2 cohorts: cohort "A" received web-based instruction on 2 urological topics through a case whereas cohort "B" received web-based instruction on the 2 other urological topics.…”
Section: Study Characteristics and Results Synthesismentioning
confidence: 99%
“…Preferably, the study also includes a ''control'' group of randomly selected students who do not attend the course, to control for possible learning of the subject matter outside the classroom (e.g., Rickard et al 1988). Alternatively, two types of educational interventions (e.g., a traditional and an innovative course) are compared for long-term knowledge retention (e.g., Holcomb et al 1982;Kerfoot et al 2006;Sinclair 1965). At course completion, all participants are posttested.…”
Section: Laboratory Experimentsmentioning
confidence: 99%